Meta-Xylene-Based Diamines with Protected Benzyl Sites: Potential NCN Pincer Ligands with Tunable Steric Profiles - Tamina Z. Kirsch; Toren Hynes; Jason D. Masuda; Saurabh S. Chitnis (Molecules)
Bulky NCN aryl-diamides featuring methyl groups in the benzyl positions were synthesized with the aim of creating a new class of meta-xylene-based trianionic pincer ligands where the common decomposition pathway of metal pincer complexes via C-H activation is prevented. Sterically demanding substituents on the ligands furthermore provide steric protection of the metal centre and can help prevent the dimerization of the complexes. While a double deprotonation of the ligands and the formation of a dilithium salt was straightforward, difficulties were encountered when attempting to deprotonate the ipso-CH proton on the central aryl ring to yield trianionic ligands. This stands in contrast to related pincer ligands without methyl groups in the benzylic positions. Experimental and theoretical investigations led to the conclusion that the challenges encountered when attempting the third deprotonation are likely caused by an interplay of increased electron density at the nitrogen atoms and steric hindrance. Both effects originate in the introduction of methyl groups in the benzylic positions, which make the targeted proton less accessible. These results provide further insight into the impact of methyl groups in the benzyl positions on both steric and electronic properties of NCN pincer ligands, which may find utility in coordination chemistry applications where metalation can be achieved by direct C-H activation rather than requiring triple deprotonation.